Legal issues in charity mergers in England and Wales, 2000 - Warburton, Jean (UK Data Service, 2003)
This study examined the legal problems charities encounter when they attempt to merge with another charity and the means used to deal with them. Using an extensive literature review and in-depth qualitative interviews, the research had four aims: firstly, to identify as far as possible a preliminary list of the legal issues in charity mergers; secondly, to use qualitative interview techniques to gather data on the practical experience of such mergers and the effects they had on participants; thirdly, to produce a guide to good legal practice, giving an illustration of both routine and unprecedented legal problem solving; finally, to contribute towards more informed policy making in the voluntary sector. Before the final guide to good legal practice was produced, research participants were invited to attend, or contribute to, a conference. This dealt with best practices in relation to the legal issues identified. The conference included both a plenary session and small discussion groups focus. The aim of the conference was to finalise which of the different approaches to legal issues was considered to be the best practice. A full research report and guide to good legal practice is available to accompany the dataset, and forms part of the user guide.